The Decelopment of Computer Assited Instruction Based on Brain-Based Learning Theory on Topic: Types of Words In Thai Language For Prathom Suksa 5 Students. - Sopa, Mana; Butdeehat, Kanyarat; Phansaensao, Fuangfa (Walailak Journal of Learning Innovations, 2019)
The purposes of this research were 1) to develop the Computer Assisted Instruction (CAI) based on Brain-Based Learning (BBL) theory on topic: Types of Words in Thai Language for Prathom Suksa 5 Students, 2) to compare pretest-posttest students learning achievement with CAI, and 3) to study student’s satisfaction with CAI. The sample group was conducted under the purposive sampling technique and consisted of 26 in Prathom Suksa 5 students from Ban Nong Kham School (Khai Seni Uppatham), who were studying in second semester of the academic year 2018. The research tools included: 1) developed CAI based on BBL theory. 2) Learning achievement test which a multiple choice quizzes, 4 choices, 30 items 3) Sub chapters test which a multiple choice quizzes, 4 choices, 30 items and 4) student’s satisfaction rating scales 5 levels questionnaire for CAI, 10 items. Statistics used for data analyses were mean, percentage, standard deviation, Efficiency (E1/E2), and t-test dependent samples. The results showed that: 1) the developed CAI had efficiency at 81.41/84.62. 2) The learning achievement had posttest score higher than pretest score at significant level .05 and 3) the satisfaction of sample groups also showed at high level (mean= 4.00, S.D. = 0.95)